Optimisation tools for meeting nutrient requirements of Indian children and adults at optimal cost - Fathima Ayoob; Jawahar R. Manivannan; Ashikh Ahmed; Afsal K. Murikkanchery; Abhishek Kumar; Santu Ghosh; Patrick Webb; Anura V. Kurpad; Tinku Thomas (Public Health Nutrition)
Abstract